Effect of fuel injection characteristics on the performance of a free-piston diesel engine linear generator: CFD simulation and experimental results. (15th March 2018) - Guo, Chendong; Song, Yu; Feng, Huihua; Zuo, Zhengxing; Jia, Boru; Zhang, Ziwei; Roskilly, A.P.
Highlights: The trends of the compression ratio, peak in-cylinder pressure and IMEP of the FPDLG are the convex curves. When the injection timing reaches to 8 mm, the combustion heat release reduces by 94.5%. The trapezium injection rate-profile can keep high efficiency of the FPDLG. Abstract: The free-piston diesel engine linear generator (FPDLG), as a novel energy conversion device, is investigated by many researcher groups. The injection characteristics are important for the FPDLG operation performance. Therefore, the effects of fuel injection characteristics on the FPDLG are researched by CDF simulation and experimental results in this paper. According to the results, it is found that the trends of the compression ratio and the peak in-cylinder pressure vs the injection timing are the identical with convex function curves. And the IMEP of the FPDLG also show the same trend. Although the heat-release rises in the rapid combustion period, the IMEP vs the injection timing various law present convex function curve on account of reduced heat-release in the normal combustion period. Four injection rate-profiles, i.e. rectangle, wedge, trapezium and triangle are simulated and compared. It is observed that the combustion process with the trapezium rate-profile curve is smoother. The peak in-cylinder pressure and the thermal efficiency can be kept high value while the center of heat-release curve near the TDC. Therefore the trapezium rate-profile is suggested is appropriate and can keep high efficiency of the FPDLG in order to get high engine efficiency.